Multi-couple group and self-directed PREP formats enhance relationship satisfaction and improve anger management skills in Air Force couples - Anderson, Jared R.; Stith, Sandra M.; Johnson, Matthew D.; Strachman- Miller, Marjorie M.; Amanor-Boadu, Yvonne; Linkh, David J. (My University, 2013)
This study examined the effectiveness of delivering the Prevention and Relationship Enhancement Program (PREP) to volunteer couples in the U.S. Air Force in either a six-week instructional multi-couple group condition or a self-directed book condition. A standardized pre/post protocol was employed and outcomes included relationship satisfaction and anger management skills, two known risk factors for partner maltreatment. Significant improvement was found for the group condition in both relationship satisfaction and anger management skills, but only for anger management skills in the self-directed book condition. Finally, the group condition reported greater program satisfaction. Implications are discussed.
Keywords: Relationship education; Air Force; Relationship satisfaction; Anger management skills